Food science an ecological approach - Edelstein, Sari (Jones & Bartlett Learning, 2014)
A textbook at the forefront of a global movement toward sustainability Food Science, An Ecological Approach presents food science and food preparation in the context of current environmental world conditions. Throughout the text readers will examine the scientific basis of the dietetics profession and thoroughly explore food chemistry, preparation, safety, regulations, and cultural significance. The science of food is discussed within the broader context of the world's food supply. Food Science, An Ecological Approach explores the idea of global sustainability and examines the ecological problems that challenge our food supply and raise increasing concerns among consumers. Each chapter sets out clear objectives and integrates helpful sidebars, illustrations and discussion questions to increase concept retention. Chapter summaries and special sections found throughout the text engage students and enhance the learning experience. Additional resources are available online which complement the text.